A simple assessment of enthalpy of fusion of non-aromatic organic compounds as smokeless fuels for correcting thermochemical data to a standard state. (15th May 2023) - Keshavarz, Mohammad Hossein; Nazari, Behzad; Farashbandian, Neda
Graphical abstract: Prediction of enthalpy of fusion of non-aromatic organic compounds versus the measured values by the new model and the best comparative method. Highlights: A simple correlation is introduced for reliable prediction of enthalpy of fusion of non-aromatic organic compounds. They can be easily evaluated from molecular structures of non-aromatics. The largest available reported data are used to derive and test the new model. The high reliability of the new models is proved in comparison with the best available method. The robustness of the new model is confirmed by various statistical parameters. Abstract: The knowledge of the enthalpy of fusion of different categories of non-aromatic organic compounds, which have wide applications as smokeless fuels, is important in Chemical Thermodynamics but its experimental determination is complicated. An improved model is developed based on the additive contribution of different atoms of a non-aromatic compound with the general formula C a H b N c O d S e F f Cl g Br h I i and two non-additive correcting parameters. The largest reported data of 639 non-aromatic organic compounds (corresponding to 949 experimental values) were collected from different sources to derive and test the new model. Errors maximum value (ErrorMax), root-mean-square error (RMSE), and mean error (ME) of the new model are compared with one of the best methods for 513 and 126 data of two sets of training and test, respectively. ErrorMax, RMSE, and ME values of the novel method for training/test sets are 19.68/16.24, 4.393/4.668, and 0.000/0.230, respectively, but the results of the comparative model are 39.74/26.00, 7.004/5.666, and 1.645/1.940, respectively. The results confirmed that the new model can predict the enthalpy of fusion of non-aromatic organic compounds more accurately than a more complex comparative method.